2018
DOI: 10.3390/socsci8010005
|View full text |Cite
|
Sign up to set email alerts
|

Gender Equality in Europe and the Effect of Work-Family Balance Policies on Gender-Role Attitudes

Abstract: This study starts from the assumption that the context of opportunities for work-family balance affects individual attitudes toward gender roles, a main indicator of support for gender equality. Compared with extant research, the present study adopts a more articulated definition of “opportunity structure” that includes national income level and social norms on gender attitudes, measures of gender-mainstreaming policies implemented at the company level (flextime), and different work-family balance policies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 93 publications
2
24
0
9
Order By: Relevance
“…This supports the argument that when mothers' underemployment is studied, questions related to the organization of childcare should be taken into account (see also Kjeldstad and Nymoen 2012). However, it should be noted that the childcare coverage variable actually measured the use of childcare (Lomazzi et al 2018). Hence, more precisely, the probability of being underemployed increases by one percentage point when the usage of childcare decreases by one percentage point.…”
Section: Resultssupporting
confidence: 69%
“…This supports the argument that when mothers' underemployment is studied, questions related to the organization of childcare should be taken into account (see also Kjeldstad and Nymoen 2012). However, it should be noted that the childcare coverage variable actually measured the use of childcare (Lomazzi et al 2018). Hence, more precisely, the probability of being underemployed increases by one percentage point when the usage of childcare decreases by one percentage point.…”
Section: Resultssupporting
confidence: 69%
“…'Gender contracts' reflecting households' arrangements in balancing paid work and care work are not simply a result of individual preferences. The outcome of the partners' negotiations is a combination of practices, norms, values, structural factors and institutional opportunities (Aboim, 2010;Dingeldey, 2016;Lomazzi et al, 2018;Pfau-Effinger, 2005). Nonetheless, the worse situational job characteristics of women do not necessarily lead to lower job satisfaction.…”
Section: Job Satisfaction: Work and Non-work-related Factors Of Explamentioning
confidence: 99%
“…Previous research demonstrated that the nexus between individual gender role attitudes and the societal context is particularly relevant, both considering the structural and the cultural orientation of a country. On one hand, the societal structure of opportunity, such as the availability of daycare services, parental leave schemes, or labor market conditions, affect attitudes toward gender roles (André et al, 2013; Lomazzi et al, 2019; Kangas & Rostgaard, 2007; Sjöberg, 2004). On the other hand, gender role attitudes are connected with broader value orientations, which can differ vastly across societies according to their cultural, social, and political history (Inglehart, 1997; Kalmijn, 2003; Pfau-Effinger, 2004; Schwartz, 2006).…”
Section: Summary and Discussionmentioning
confidence: 99%